2017
DOI: 10.1111/1753-0407.12520
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in patients with diabetes 10 years after liver transplantation

Abstract: In the present study diabetes was associated with a higher risk of liver graft rejection and cardiovascular events. There was also a trend for higher mortality, although the effect was not statistically significant. These findings suggest that patients with diabetes require a more rigorous pretransplant evaluation and closer monitoring after transplantation in order to try to reduce associated complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In addition, we noted no impact of BMI on both all‐cause mortality and cardiovascular‐related mortality when BMI <30 and BMI ≥30 were compared. The presence of type 2 diabetes has been associated with an increased risk of adverse post‐transplant outcomes in an earlier study using the SRTR (The Scientific Registry of Transplant Recipients) data . Another study using UNOS data noted obesity alone was not associated with lower post‐transplant survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we noted no impact of BMI on both all‐cause mortality and cardiovascular‐related mortality when BMI <30 and BMI ≥30 were compared. The presence of type 2 diabetes has been associated with an increased risk of adverse post‐transplant outcomes in an earlier study using the SRTR (The Scientific Registry of Transplant Recipients) data . Another study using UNOS data noted obesity alone was not associated with lower post‐transplant survival.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of DM on long‐term survival of the transplant recipients has been reported . Diabetes has been associated with a higher risk of liver graft rejection and cardiovascular events . Despite evidence for such association with diabetes, a recent study has also reported no impact of diabetes on the post‐transplant outcome .…”
Section: Discussionmentioning
confidence: 99%
“…Pretransplant diabetes is a predictor of poor outcome following liver transplantation ( 4 ). One recent study reported that patients with diabetes have a higher risk of liver graft rejection ( 5 ). Diabetes mellitus is also a major risk factor involved in ischemic diseases affecting multiple organs, including the heart ( 6 ), brain ( 7 ), kidney ( 8 ), and liver ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, patients with sustained post-transplant diabetes had significantly increased risk of major cardiovascular events after OLT, with HR 1.95, and cumulative risk of 13% and 27% at 5 and 10 years after OLT, respectively [16]. Ramos-Prol et al reported a trend for higher mortality in liver graft recipients with diabetes, showing to the need for more rigorous pretransplant evaluation and closer monitoring after OLT in order to reduce associated complications in diabetics [17]. Additionally, transplanted patients with hepatitis B-related hepatocellular carcinoma and diabetes mellitus had decreased survival and poor OLT outcomes at 1, 3, and 5 years after the procedure [18].…”
Section: Discussionmentioning
confidence: 99%